2021
DOI: 10.1155/2021/8858165
|View full text |Cite
|
Sign up to set email alerts
|

Afrostyrax lepidophyllus Mildbr. and Monodora myristica (Gaertn.) Dunal Extracts Decrease Doxorubicin Cytotoxicity on H9c2 Cardiomyoblasts

Abstract: Ethnopharmacological Relevance. Doxorubicin (Dox) is an anthracycline antibiotic widely used in cancer treatment. Despite its antitumor efficacy, its clinical application is significantly limited because of its cardiotoxicity originated, among other factors, from pro-oxidant damage to cardiac mitochondria. Phytochemicals represent a potentially attractive strategy to mitigate Dox cardiotoxicity due to their antioxidant properties, with plant extracts used in traditional medicine often being ignored in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…The overexpression of Caspase-3 may ultimately induce apoptosis responses. Essential oils present in plant extracts can remarkably induce Caspase-3-dependent apoptosis properties and examples of such plant extracts include, but are not limited to, Afrostyrax lepidophyllus Mildbr, Monodora myristica, Arachis hypogaea, Ricinus communis L. Garcinia epunctata and Ptycholobium contortum [34][35][36][37].…”
Section: In Vitro Gene Expression Profiling Of Caspasementioning
confidence: 99%
“…The overexpression of Caspase-3 may ultimately induce apoptosis responses. Essential oils present in plant extracts can remarkably induce Caspase-3-dependent apoptosis properties and examples of such plant extracts include, but are not limited to, Afrostyrax lepidophyllus Mildbr, Monodora myristica, Arachis hypogaea, Ricinus communis L. Garcinia epunctata and Ptycholobium contortum [34][35][36][37].…”
Section: In Vitro Gene Expression Profiling Of Caspasementioning
confidence: 99%
“…Te fnding could be confrmed with the trend of the result recorded with the evaluation of the TPC presented in paragraph 3.2. Moukette et al [4] previously studied the TPC of A. lepidophyllus and discovered that they were mainly made up of favonoids which are powerful antioxidant compounds. Te best method which exhibited the highest AOA was found to be pot roasting for 15 min.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…Te leaves are crushed, infused, and used as bath seat to fght against women hemorrhoids and as mouthwash to treat caries and toothache. Te authors in [4] reported cytotoxic and antimicrobial activities of the essential oils from the A. lepidophyllus seeds. Te polyphenol content of the hydroethanolic bark extract of this plant is greater than 28 mg/g with about 7 mg/g being favonoids [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation